Classroom Techniques in Teaching by the Case Method - Charan, Ram (Academy of Management Review, 1976)
In this article the author outlines a method, which builds on pervious research on teaching by case method, for conducting a successful classroom discussion in a business policy course. He notes that teaching is largely an individual process; however, building a framework is important, especially for longer courses. The author outlines a three step process for establishing this framework starting with course design, class preparation and finally a method of conducting class discussions. He provides extensive details into each of these areas, essentially presenting an overview on how to conduct a class from beginning to end. He closes by noting that to effectively teach by case method the instructor must be fully prepared.